Molecular characterization and phylogeny of Shiga toxin-producing Escherichia coli derived from cattle farm - Zhang, Shiqin; Bai, Zhiye; Wang, Zichen; Wang, Xiang; Wang, Wen; Li, Hongmei; Dong, Qingli (Frontiers in Microbiology, 2022)
Shiga toxin-producing Escherichia coli (STEC) is an important food-borne pathogen, which can cause diseases such as diarrhea, hemorrhagic enteritis and hemolytic uremic syndrome in humans. Twelve STEC isolates were collected from beeves and feces of commercial animals in China between 2019 and 2020 for this study. In addiation to determination of serotype and Shiga toxin subtype, whole genome sequencing (WGS) was used for determining phylogenetic relationships, antimicrobial resistance (AMR), virulence genes and sequence type (ST) of isolates. A total of twenty-seven AMR genes were datected, and each STEC isolate carried more than ten AMR genes. Eight STEC isolates from ground beef and four STEC isolated from feces were screened. A total of seven serotypes were identified, and one isolate ONT:H10 was undetermined by SeroTypeFinder. Three O157:H7 strains were confirmed and the remaining five serogroups were confirmed as O26:H11, O81:H31, O105:H8, O178:H19, O136:H12. The phylogenetic analysis showed that STEC isolates of the same serotype or ST were clustered together based on cgMLST. Comparation of the genomes of 157 STEC reference isolates worldwide with our local STEC isolates showed that STEC isolates screened in China represented a virous collection and could not form a separate cluster but were interspersed among the STEC reference collection, which suggested that several STEC isolates shared a common ancestors irrespective of STEC serotype isolates. cgMLST revealed that isolates of the same O serotype clustered irrespective of their H type. Further investigation is required to determine the pathogenic potential of other serotypes of STEC particularly in regards to these rare serotypes. Keywords: STEC; Food; cgMLST; Serogroups; Phylogenetic relationships